A MILP-Based Approach for Virtual Microgrid Restoration - Ali Bu Jubarah; Mohammad Al-Muhaini; Ibrahim Mohammed Elamin (IEEE Access, 2020)
There has been a sharp increase in the demand for energy in recent years as a result of technological and societal advances, requiring continuous updates to the power system networks. Greater reliance on renewable energy (RE) sources is seen as a viable way to minimize the dependency on conventional sources, which also plays a significant role in increasing system reliability and reducing the environmental pollution. The system resulting from merging RE sources with the distribution system (DS) should have the ability to isolate and restore the power when faults occur. In this paper, we propose a smart restoration technique for the virtual microgrid networks. The motivation of the proposed technique was derived from merging the concept of fault management in the microgrid system and participating in the energy market (EM) in virtual power plant (VPP) networks, and the technique is referred to as the virtual microgrid system. Several factors are considered in the study, including the maximum load demand, the available power supply, and the operation cost. The restoration problem is posed as a Mixed Integer Linear Programming (MILP) problem. The system is implemented as an IEEE 13 bus system and it is assumed to be a smart virtual microgrid system that consists of automated devices, such as automated switches, computer-based remote control, and sensors.